Development of a Hybrid Learning Virtual Space Module Based on Local Saluan Language Wisdom in Science Education for Elementary School Students - Kadek Hariana; Pahriadi Pahriadi; Yun Ratna Lagandesa; Asriani Asriani; Sisriawan Lapasere; Supriyadi Supriyadi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to develop a hybrid learning virtual space design based on local Saluan language wisdom in science subjects for fifth grade students at SDN 3 Luwuk. The research method used is development research using the Borg and Gall model. Development steps include requirements analysis, design, development, implementation, and evaluation. The hybrid learning virtual space design developed contains science learning materials with content related to the local wisdom of the Saluan ethnic language. Learning material is presented in interactive multimedia form and equipped with various activities that can increase student participation in the learning process. Evaluation is carried out by measuring the quality of the hybrid learning virtual space in terms of effectiveness, efficiency and student satisfaction. It is hoped that this research can provide interesting learning alternatives and can increase the interest and learning outcomes of fifth grade students at SDN 3 Luwuk in science subjects by utilizing the local wisdom of the Saluan ethnic language. The targeted outcomes of this research are (1) design of a hybrid learning virtual space based on local wisdom of the Saluan language in science subjects for fifth grade students at SDN 3 Luwuk; (2) teaching materials and learning media that can improve student learning outcomes, interest and motivation; (3) alternative science learning media with hybrid learning virtual space; (4) increasing local wisdom in learning